THE INFLUENCE OF ONLINE TO OFFLINE LEARNING METHODS ON LEARNING MOTIVATION IN MUSLIM DOCTORS, FACULTY OF MEDICINE, YARSI UNIVERSITY - Salsabila, Ayudhia; Citra Fitri Agustina (Jurnal Penelitian, 2024)
Background: Online learning is implemented as an effort to reduce the spread of Covid-19. In the medical education, coass, online learning affects the learning motivation of students. Motivation is the drive to perform an action with a specific goal. The goal of this research is to understand the learning motivation of Muslim doctors during the transition from online to offline learning methods during clinical clerkship. Method: This research is quantitative, using the Wilcoxon test by distributing the Motivated Strategies for Learning Questionnaire (MSLQ) online. The research sample consists of Muslim doctors from the Faculty of Medicine, YARSI University in 2022, learning with the transition from online to offline methods during clinical, selected through simple random sampling. Result: The results obtained in this study show that the learning motivation during online learning is mostly categorized as very good compared to offline learning Conclusion : The score of learning motivation from online to offline does not show significant changes, with a significance value of 0.812 > 0.05, indicating no increase in learning motivation during the transition from online to offline learning methods.